Decreased activity in zebrafish larvae exposed to glyphosate-based herbicides during development—potential mediation by glucocorticoid receptor - Spulber, S.; Reis, L.; Alexe, P.; Ceccatelli, S. (Frontiers in Toxicology, 2024)
Glyphosate-based herbicides (GBH) are a widely used group of pesticides that have glyphosate (GLY) as main active compound and are used to control a wide range of weeds. Experimental and epidemiological studies point to neurotoxicity and endocrine disruption as main toxic effects. The aim of this study was to investigate the effects of developmental exposure to GLY and GBH on locomotor behavior, and the possible contribution of GR-mediated signaling. We used zebrafish (Danio rerio) larvae in a continuous exposure regimen to GLY or GBH in the rearing medium. Alongside TL wildtype, we used a mutant line carrying a mutation in the GR which prevents the GR from binding to DNA (grs357), as well as a transgenic strain expressing a variant of enhanced green fluorescent protein (d4eGFP) controlled by a promoter carrying multiple GR response elements (SR4G). We found that acute exposure to GBH, but not GLY, activates GR-mediated signaling. Using a continuous developmental exposure regime, we show that wildtype larvae exposed to GBH display decreased spontaneous activity and attenuated response to environmental stimuli, a pattern of alteration similar to the one observed in grs357 mutant larvae. In addition, developmental exposure to GBH has virtually no effects on the behavior of grs357 mutant larvae. Taken together, our data indicate that developmental exposure to GBH has more pronounced effects than GLY on behavior at 5 dpf, and that interference with GR-mediated signaling may have a relevant contribution.